CHILDREN BORN IN PRISON, THEIR LIFE TRAJECTORIES: THE PENAL ASPECT - Nesterov, Artyom (Scientific Journal of Pedagogy and Economics, 2021)
the article is devoted to the problems of keeping and resocialization in the penitentiary system of Russia, imprisoned women with young children aged from birth to three years. The author provides statistical data for 2014-2020 regarding women prisoners and their children in the system of the Federal Penitentiary Service of Russia. The problems of resocialization and post-penitentiary adaptation of children born in penitentiary institutions of the Federal Penitentiary Service of Russia are analyzed. Thus, in the penitentiary institutions of the Federal Penitentiary Service of Russia, in which convicted women with children are serving their sentences, mother and child homes are organized. In the homes of mothers and children of correctional colonies for convicted women, the conditions necessary for the normal life and development of children are provided. For women with an infant under investigation in the "Investigative Isolation" of the Federal Penitentiary Service of Russia, special cell-type units are being equipped for keeping newborns and their mothers. The author conducted a questionnaire survey of female convicts of the "Correctional Colonies" of the Federal Penitentiary Service of Russia. Topic of the program: "Features of the penitentiary adaptation of convicted women with children". Selective survey by the method of questioning - n = 270; interviewing - n = 55 respondents - convicted mothers who gave birth in places of detention (2014-2020). The age of the respondents is 20-40 years old. The respondents’ answers were processed using the SPSS software package. The article analyzes the life trajectories of children born in prisons. At the end of the publication, a transcript of the author’s conversation with a minor who is currently being brought up in boarding schools for orphans is presented. The author’s conclusions and proposals are made for the improvement of criminal-executive Russia, in particular for women prisoners with children under the age of three years. The article was prepared in the scientific specialty of the Higher Attestation Commission of the Ministry of Science and Higher Education of the Russian Federation: 12.00.08 - “Criminal law and criminology; penal law". The presented material in the publication does not contain information related to state secrets of the Russian Federation.